2020
DOI: 10.1101/2020.06.19.161042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drug repurposing screens reveal FDA approved drugs active against SARS-Cov-2

Abstract: There are an urgent need for antivirals to treat the newly emerged SARS-CoV-2. To identify new candidates we screened a repurposing library of ~3,000 drugs. Screening in Vero cells found few antivirals, while screening in human Huh7.5 cells validated 23 diverse antiviral drugs. Extending our studies to lung epithelial cells, we found that there are major differences in drug sensitivity and entry pathways used by SARS-CoV-2 in these cells. Entry in lung epithelial Calu-3 cells is pH-independent and requires TMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
99
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(102 citation statements)
references
References 111 publications
3
99
0
Order By: Relevance
“…Two groups performed genome-wide CRISPR-Cas9 screens to identify host factors required by SARS-CoV-2 (Heaton et al, 2020;Wei et al, 2020) with the hope that these screens would not only uncover the biology underlying this virus, but also identify druggable host factors that could be targeted to prevent virus spread or lessen disease. Other groups conducted drug repurposing screens using compound libraries enriched with FDA-approved or clinical phase drug candidates to identify off-theshelf interventions (Dittmar et al, 2020;Zhou et al, 2020). A complementary strategy to these screens is to nominate candidate host factors that are predicted to interact with viral proteins through immunoprecipitation mass spectrometry (IP-MS) of affinity tagged viral proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Two groups performed genome-wide CRISPR-Cas9 screens to identify host factors required by SARS-CoV-2 (Heaton et al, 2020;Wei et al, 2020) with the hope that these screens would not only uncover the biology underlying this virus, but also identify druggable host factors that could be targeted to prevent virus spread or lessen disease. Other groups conducted drug repurposing screens using compound libraries enriched with FDA-approved or clinical phase drug candidates to identify off-theshelf interventions (Dittmar et al, 2020;Zhou et al, 2020). A complementary strategy to these screens is to nominate candidate host factors that are predicted to interact with viral proteins through immunoprecipitation mass spectrometry (IP-MS) of affinity tagged viral proteins.…”
Section: Introductionmentioning
confidence: 99%
“…This choice was driven by the following: 1., favorable side-effect profile, 2 nd generation non-sedating in most individuals, 2., no major effect on normal physiology, since the indication is to alleviate allergy symptoms, 3., broad availability, wide use, low cost; 4., availability in a nasal formulation for potential effect on nasal colonization; 5., several H1 and H2 blockers identified in our screens and others, e.g. ebastine 8,28 ; and 6., positive clinical data with the H2 receptor antagonist famotidine. 21 Here we provide experimental proof that azelastine is effective against SARS-CoV-2 infection in the most widely employed in vitro assay system with Vero E6 cells with comparable EC50 value (~6 µM) determined for chloroquine, lopinavir, and remdesivir (7 to 11 µM) using the same cell line.…”
Section: Discussionmentioning
confidence: 60%
“…23 Several of the drugs predicted in this study have been shown to have activity against coronaviruses in vitro. Cepharanthine, a natural compound with anti-inflammatory and antineoplastic activities was identified in a recent large-scale high throughput COVID-19 drug repurposing project using libraries of ~3000 drugs (~1000 of these FDA approved drug) 8 and also by others. 24,25 Previous studies demonstrated its inhibitory effects on both SARS-CoV 26 and HCoV-OC43.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations